Praktikalitas dan Efektivitas Media Augmented Reality Materi Pergeseran Kesetimbangan Kimia terhadap Hasil Belajar Peserta Didik - Eksa Priani; Guspatni Guspatni; Nofri Yuhelman (Lembaga Yasin AlSys, 2025)
Augmented Reality (AR)-based learning media have demonstrated potential in enhancing the understanding of abstract chemical concepts, such as chemical equilibrium. This study aims to evaluate the practicality and effectiveness of AR-integrated learning media previously validated in an earlier study. A pre-experimental method with a one-group pretest–posttest design was employed. Practicality testing involved 9 students and 2 chemistry teachers at SMA Negeri 1 Tiumang, while effectiveness was assessed based on the improvement of student learning outcomes using N-Gain analysis and t-test. The sample was selected through purposive sampling, and data collection was conducted at SMA Negeri 1 Koto Baru. The results indicate that the media were rated as highly practical by both teachers (86%) and students (81%), with an N-Gain score of 0.49, classified as moderate. The t-test revealed a significant difference between pretest and posttest scores. Thus, the AR learning media are considered practical and effective, contributing positively to chemistry instruction, particularly in the topic of equilibrium shift.